Driving Customer Loyalty through Engagement - Gubrele, Astha; Tripathi, Rajendra (Journal of Advanced Research in Strategic Marketing Intelligence and Customer Engagement Optimization, 2025)
Customer loyalty has become a critical factor in driving business success, particularly in today’s highly competitive markets. One of the most effective ways to foster customer loyalty is through optimized engagement. This review article explores how businesses can enhance customer engagement through personalized experiences, technological integration, and data-driven strategies. By optimizing engagement, companies can deepen customer relationships, increase retention, and drive long-term brand loyalty. This article examines key strategies, the role of technology, and best practices in engagement optimization, while also addressing the challenges that businesses face in creating lasting loyalty.